Ralph David Kopperman, 1942-2021 - Andima, Susan; Pajoohesh, Homeira; Wilson, Richard (Topology Proceedings, 2022)
Professor Ralph David Kopperman died on February 6, 2021 at the age of 78, a victim of the SARS-Covid-2 pandemic. He will be greatly missed, most dearly by his wife Connie and his five adult children, but also by the wider mathematical and computer science communities and his many co-authors (MathSciNet lists 58 of these), including, of course, the three authors of this article of remembrance.